2022
DOI: 10.1002/adbi.202101327
|View full text |Cite
|
Sign up to set email alerts
|

Sars‐Cov‐2 Spike Protein‐Induced Damage of hiPSC‐Derived Cardiomyocytes

Abstract: Sars-Cov-2 may trigger molecular and functional alterations of cardiomyocytes of the heart due to the presence of receptor angiotensin-converting enzyme 2 (ACE2) of the host cells. While the endocytic itinerary of the virus via cleavage of the spike protein of Sars-Cov-2 is well understood, the role of the remaining part of the spike protein subunit and ACE2 complex is still elusive. Herein, we investigate the possible effects of this complex by using synthetic spike proteins of Sars-Cov-2, human induced pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Clough et al found that the S protein increased expression of caspase 3/7 in human microglial cells suggesting increased apoptosis ( Clough et al, 2021 ). Huang et al found that the S protein induced nuclear fragmentation in cardiomyocytes, which is a prominent feature of cellular necrosis and apoptosis ( Huang et al, 2022 ). Consistent with the findings of Clough et al, Nuovo et al found that S1, but not S2 injected IV induces caspase-3 in mouse brain endothelial cells, suggesting increased apoptosis.…”
Section: Sars-cov-2 Glycoproteins Function As Pampsmentioning
confidence: 99%
“…Clough et al found that the S protein increased expression of caspase 3/7 in human microglial cells suggesting increased apoptosis ( Clough et al, 2021 ). Huang et al found that the S protein induced nuclear fragmentation in cardiomyocytes, which is a prominent feature of cellular necrosis and apoptosis ( Huang et al, 2022 ). Consistent with the findings of Clough et al, Nuovo et al found that S1, but not S2 injected IV induces caspase-3 in mouse brain endothelial cells, suggesting increased apoptosis.…”
Section: Sars-cov-2 Glycoproteins Function As Pampsmentioning
confidence: 99%
“…RT-qPCR analysis of the post-transplanted COs confirmed the loss of cardiac muscle cells, evidenced by lower expression of TNNT2 and ACTN2. (41) Meanwhile, the fibrosis-related genes such as COL1A1, COL3A1, MMP-9, MMP-2 and α-SMA, (44)(45)(46) and genes that are related to inflammation: IL-1 β and IL-6 were detected to be upregulated after the spike 1+ang II treatment (Fig. 4F), which aligned with the physiological response within the human body.…”
Section: Cos Modelled Myocardial Infarction and Sars-cov-2 Induced Fi...mentioning
confidence: 55%
“…The impact of SARS-CoV-2 Spike protein on cellular functions is of key interest, as the two mRNA vaccines BNT162b2 from Pfizer-BioNTech and mRNA-1273 from Moderna, generate high levels of this protein [14,[22][23][24]. Therefore, searching for circulating Spike in plasma of COVID-19 patient might help in understanding unexpected adverse effects following COVID-19 mRNA vaccination [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to this issue are reported evidences of circulating Spike Protein detected in post-COVID-19 mRNA vaccinated subjects [18][19][20][21][22][23], and several reports outlining that Sprotein affects cellular metabolism and gene expression in a variety of tissue systems [12,[24][25][26][27][28][29], including the hematopoietic system [28,29]. Accordingly, the effects of SARS-CoV-2 infection and/or vaccination on the hematopoietic system should be carefully considered [28][29][30].…”
Section: Introductionmentioning
confidence: 99%